Creative Leadership and Institutional Excellence in the Digital Transformation Era: A Systematic Review - Alshammari, Huda Maazi (Journal of Ecohumanism, 2025)
The rapid advancement of digital technologies has necessitated innovative leadership approaches to enhance institutional performance and maintain competitiveness. Creative leadership plays a crucial role in navigating the complexities of digital transformation by fostering an environment of innovation, adaptability, and continuous learning. This study examines the impact of creative leadership on institutional performance within the context of digital transformation at Qatar University. Through a systematic review, the research explores how creative leadership influences the adoption of digital transformation strategies and their subsequent effects on institutional efficiency and effectiveness. The study highlights key initiatives at Qatar University, including partnerships with Coursera and Google Cloud, to enhance digital learning and faculty development. Findings suggest that creative leadership facilitates a culture of innovation, supports digital engagement, and strengthens industry-academia collaboration, ultimately contributing to improved institutional performance. The study offers theoretical insights into the relationship between creative leadership and digital transformation while providing practical recommendations for higher education institutions seeking to optimize their leadership strategies in the digital era.